Russian Public Assembly Law: Constitutional Evolution 1993–2023 - A. Salenko (BRICS Law Journal, 2024)
The current Public Assembly Law in the Russian Federation, which regulates the implementation of the constitutional right to freedom of peaceful assembly in Russia, has been developed and formed over the course of the past three decades, following the ratification of the Russian Constitution in 1993. The Public Assembly Law can be described as an important institute of public law as well as a sub-branch of the constitutional law of Russia, which combines constitutional provisions, relevant norms of the federal and regional laws and case law of the Russian Constitutional Court regarding the implementation of the Freedom of Peaceful Assembly. The modern Public Assembly Law has high importance for the development of a democratic society and for the rule of law. The author investigates the constitutional adjudication of the Russian Constitutional Court from 1993–2023, focusing in particular on its eleven judgments concerning the implementation of Article 31 of the Russian Constitution, which defines the constitutional standards of the Freedom of Peaceful Assembly. The author also examines several prominent cases of the Russian Constitutional Court, referred to as decisions with positive content, which are crucial for obtaining a systemic overview of the current problems of the Public Assembly Law in the Russian Federation.